Performance Analysis of a Mechanical System To Break and Separate Palm Nut-Fibre Cake - Prince Yaw Andoh Andoh; Kofi Owura Amoabeng; Charles Kofi Kafui Sekyere; D E K Dzebre (Journal of Applied Engineering and Technological Science (JAETS), 2022)
This research seeks to test the performance of a palm nut-fibre cake breaker and separator machine to alleviate the problem of hand separation by local oil producers. It takes into consideration the standard cylindrical shape of a palm nut-fibre cake. The machine operated on an electric motor of 2.2 kW at 1420 rpm. The average throughput capacity of the machine was 107.72 kg/hr with the capacity weight of 120 kg. Test results indicated a separation efficiency of 92%. Also, cost estimation indicated that the annual savings in using the machine with less labour than manual labour entirely was $466. The study outcome is relevant to small-scale producers on the need to utilize a cost-effective machine to facilitate a high separation yield of nuts and fibres from the cake obtained from processing palm oil and improve the production output of palm kernel oil processed from the nuts.